ANALISIS KEBERLANJUTAN RANTAI PASOK APEL DI KABUPATEN MALANG MENGGUNAKAN DINAMIKA SISTEM - Tiara Ariqoh Bawindaputri; Retno Astuti; Endah Rahayu Lestari (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Apple production as a typical fruit of Malang Regency has decreased due to land degradation, land conversion, climate change, and old tree age. This can disrupt the apple supply chain sutainability in Malang Regency. This study aimed to produce simulations of several scenarios for the sustainable apple supply chain development and provide policy recommendations for the apple supply chain sustainability in Malang Regency. The model made consisted of 3 sub models, i.e. economic, social, and environmental. The respondents were 53 farmers, 3 collectors, and 20 retailers. The parameters measured were the profit of farmer, collectors, and retailers, employment, and the area of degraded land. Simulations were carried out in 3 scenarios from 2020 to 2030, i.e. the original conditions (scenario 1), controlling land (scenario 2), and increasing productivity and controlling land simultaneously (scenario 3). The best parameter values were obtained from the scenario 3 simulation results, i.e. adding land by 1.15%/year, reducing the conversion rate to 2.93%, and increasing productivity by 5%/year. This scenario showed that in 2030 yields 4,905,656 kg of apples with profits of farmer, collectors, and retailers were Rp 26,374,922,326, Rp 31,597,327,651, and Rp 27,996,576,448, respectively, employment of 22,349 people/hectare, and a degraded land area of 11.7 hectares. The scenario 3 implementation can reduce the decline in apple land area and productivity over the next 10 years. Policies that can be implemented include providing training and incentives for farmers, strengthening policies on apple commodities, restoring soil, and transitioning to organic farming.Keywords: apple, supply chain, sustainability, system dynamics